Developing Service Excellence Skills through the Guest Teacher Training Program at Vocational High School - Dewani, Shinta Laura; Khotimah, Arfiani Nur (Jurnal Pendidikan Non formal, 2024)
One crucial competence for vocational school (SMK) students to enter the business, industry, and job sectors (DUDIKA) as a skill-based school is service excellence. The purpose of this activity and training is to enhance students' skills in implementing the concept of service excellence as a form of best service for customers. The activity was attended by 107 students and 8 teachers. The method used is qualitative, not only serving as knowledge dissemination to the community through education but also integrating input from the school through interviews, documentation, and complete participatory observation, where the author will be fully involved in what the students are doing, along with documentation. The training method employed is the Active Learning Class. The findings reveal that students experienced an improvement in understanding and skills in providing excellent service.